Safety evaluation of the food enzyme endo‐1,4‐β‐xylanase from the genetically modified Trichoderma reesei strain DP‐Nzd72 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal, 2025)
Abstract The food enzyme endo‐1,4‐β‐xylanase (4‐β‐d‐xylan xylanohydrolase; EC 3.2.1.8) is produced with the genetically modified Trichoderma reesei strain DP‐Nzd72 by Genencor International B.V. The genetic modifications do not give rise to safety concerns. The food enzyme was considered free from viable cells of the production organism and its DNA. The food enzyme is intended to be used in three food manufacturing processes. Since residual amounts of food enzyme‐total organic solids (TOS) are removed in two processes, dietary exposure was calculated only for the remaining food manufacturing process. It was estimated to be up to 0.017 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1000 mg TOS/kg bw per day, the highest dose tested, which, when compared with the estimated dietary exposure, results in a margin of exposure of at least 58,824. A search for the homology of the amino acid sequence of the endo‐1,4‐β‐xylanase to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions upon dietary exposure to the food enzyme cannot be excluded, but that the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.